Relationship between Leg Muscle Strength, Eye Foot Coordination and Sepak Sila Sepak Takraw among Students - Hasanuddin, M Imran; Kuswoyo, Dilli Dwi; Lahinda, Jori (Sportify Journal, 2022)
Sepak sila ability is a fundamental skill in sepaktakraw because it supports ball control, receiving, rally maintenance, and continuity of play. This study aimed to analyze the relationship between leg muscle strength and eye-foot coordination with sepak sila ability among students of SMP Negeri 1 Kassi, Pangkep Regency. A quantitative approach with a descriptive-correlational design was employed. The sample consisted of 60 male students from Grades I and II selected through simple random sampling by lottery. Leg muscle strength was measured using the half squat jump test, eye-foot coordination was measured through a ball-dribbling coordination test on a predetermined course, and sepak sila ability was measured based on the number of valid sepak sila touches performed within one minute. The data were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, Pearson correlation, and multiple regression with SPSS. The findings showed that leg muscle strength had a positive and significant relationship with sepak sila ability (r = 0.314; p = 0.015), while eye-foot coordination also had a positive and significant relationship with sepak sila ability (r = 0.440; p < 0.001). Simultaneously, both predictors explained 23.2% of the variance in sepak sila ability (R = 0.481; R Square = 0.232; p = 0.001). These findings indicate that sepak sila performance is more strongly supported by the integration of physical and coordinative capacities, particularly eye-foot coordination, than by leg muscle strength as an isolated factor.